Effect of processing procedure on the formation of resistant starch in tamales. (2nd June 2016) - de Dios Figueroa‐Cárdenas, Juan; Véles‐Medina, José Juan; Esquivel‐Martínez, Anaid Michelle; Mariscal‐Moreno, Rosa María; Santiago‐Ramos, David; Hernández‐Estrada, Zorba Josué
Abstract : Tamales were produced using a traditional nixtamalization process. The nixtamal was milled into masa, mixed with shortening, and boiled to prepare tamales. Enzymatic methods and DSC enthalpies were used to investigate resistant starch (RS) and starch–lipid complexes (resistant starch 5; RS5). The addition of shortening to masa showed an endotherm of lipid melting with T o ( m ), T p ( m ), and T f ( m ) of approximately 40, 44, and 50°C, respectively. Processing masa by boiling at >90°C for 2 h to make tamales showed three endotherms: one related to amylopectin retrogradation (RS3), one to starch gelatinization ( G ), and one to Type I complex (RS5). The retrograded amylopectin presented temperatures of 49, 55, and 60°C for T o(RS3), T p(RS3), and T f(RS3), respectively. The X‐ray diffraction pattern showed that during processing starch Type A complexed with lipids to form a Type V (RS5) amylose–lipid starch complex. The RS5 in tamales estimated by DSC affected blood glucose levels from in vivo tests.